2017
DOI: 10.1159/000453446
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach of Synthesizing and Evaluating the Anticancer Potential of Silver Oxide Nanoparticles in vitro

Abstract: Background: Development of novel strategies to kill cancer by sparing normal cells is of utmost importance. Apart from their known antimicrobial activity, only limited information has been recorded regarding the antitumor potential of biocompatible silver oxide nanoparticles (AgONPs). There is a need to evaluate the anticancer potential of biocompatible AgONPs in vitro. Methods: A new approach of utilizing the leaf extract of Excoecaria agallocha was used to synthesize AgONPs. This was then characterized by ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The spherical bio-AgNPs with sizes ranging from 5-50 nm showed inhibitory activities against the lymphoma Jurkat cell line, and the IC 50 was 21.05 µg/mL [132]. The B16F10 melanoma cell line was inhibited by the 20-228 nm spherical bio-AgNPs, with an IC 50 value of 7.6 ± 0.8 µg/mL, following a dose-dependent relationship [101,133]. The 100-120 nm flower-shaped AgNPs exhibited notable repressive actions against the KB oral cancer cell line, where the IC 50 was 0.6 µg/mL [134].…”
Section: Biosynthesized Agnps As Anticancer Agents In Vitromentioning
confidence: 97%
“…The spherical bio-AgNPs with sizes ranging from 5-50 nm showed inhibitory activities against the lymphoma Jurkat cell line, and the IC 50 was 21.05 µg/mL [132]. The B16F10 melanoma cell line was inhibited by the 20-228 nm spherical bio-AgNPs, with an IC 50 value of 7.6 ± 0.8 µg/mL, following a dose-dependent relationship [101,133]. The 100-120 nm flower-shaped AgNPs exhibited notable repressive actions against the KB oral cancer cell line, where the IC 50 was 0.6 µg/mL [134].…”
Section: Biosynthesized Agnps As Anticancer Agents In Vitromentioning
confidence: 97%
“…Apoptosis induced by silver nanoparticles of different tumor cells has already been reported in vitro and ex vivo, which possibly occurred because of the translocation of the silver within the nucleus [83][84][85][86]. Franco-Molina et al reported that MCF-7 breast cancer cells treated with silver colloids exhibited considerably decreased dehydrogenase activity, causing NADH/NAD + reduction [87].…”
Section: Cytotoxicity By Brine Shrimp Lethality and Mtt Assay In Vitromentioning
confidence: 97%
“…These NPs effectively inhibited cell proliferation, angiogenesis, colony formation, and spheroid formation of breast cancer cells through apoptosis induction; HIF-1α, VEGF, Cyclin D1, and STAT-3 gene down-regulation; and Caspase-9 gene up-regulation. Ag-oxide NPs synthesized utilizing an aqueous leaf extract from Excoecaria agallocha , and with anticancer potential, were evaluated by Banerjee et al [ 139 ]. These Ag-based NPs were spherical shaped and exhibited an average particle size of 228 nm.…”
Section: Cancer Evaluation Modelsmentioning
confidence: 99%
“…These Ag-based NPs were spherical shaped and exhibited an average particle size of 228 nm. They induced a growth-inhibitory effect against murine Ehrlich ascites carcinoma cells, with an IC 50 value of 1.1 ± 0.1 µg/mL at 72 h. Their cytotoxic effect was mediated via apoptosis induction as the number of annexin V-positive cells increased as a function of time [ 139 ].…”
Section: Cancer Evaluation Modelsmentioning
confidence: 99%